Atypical forms of employment and the concept of an employee in German labor law on the example of a person working via a digital platform (crowdworker) - Zboralska, Grażyna (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
German case law and legal literature also grapple with the challenges posed by the classification of employment through digital platforms, including so-called crowdworking, particularly regarding the distinction between employees and self-employed individuals. Even before the entry into force of Directive (EU) 2024/2831 of the European Parliament and of the Council of 23 October 2024 on improving working conditions in platform work, proposals for regulating the phenomenon of crowdworking and the situation of individuals employed via digital platforms had already emerged. The question of whether a crowdworker qualifies as an employee has also been addressed by the Federal Labor Court in its judgment of 1 December 2020, 9 AZR 102/20. In interpreting § 611a of the German Civil Code (BGB) in the factual circumstances of the case, the court concluded that the crowdworker performed work within the framework of an employment contract. This study presents and analyzes the positions of German legal literature and case law regarding the legal classification of employment through digital platforms and assesses the accuracy of judicial views on the matter. The study will also cover German autonomous legislative proposals in this field.